Texts added to the print of the paper book for bin Al-Jarrah: A collection and examination - Radhi, Louay Salman (Al-Adab Journal, 2022)
The paper's book is unique to Abu Abdullah Mohammed bin Daoud bin Al-Jarrah (d. 296 .h) as a major source of translations of dozens of submerged and murdered Abbasid poets, but it did not reach us completely, as parts of it were lost and appeared marred by a lack of its investigative edition, a deficiency that was among its data the existence of a saying from the book scattered in many sources, we do not stand on it in the print of it, We have gathered from these words a material that we have been working on in this research to take care of the achievement of its texts in a scientific investigation through which we aspire to provide a valuable addition to what was printed from the book Due to its importance and its place in the literary library.